Meninjau Peran Employee Engagement dalam Hubungan antara Keadilan Organisasi, Keseimbangan Kerja-Hidup, dan Kepuasan Kerja: Apakah Employee Engagement Menambah Kepuasan Kerja? - Dewi, Almas Farah Dinna; Risqianindi, Irfika Annisa; Putri, Rizky Atika Salsabila Ivabianca; Sibarani, Elisabeth Fransiska (Jurnal Manajemen dan Kearifan Lokal Indonesia, 2024)
This study aims to analyze the influence of Organizational Justice, Work-Life Balance (WLB), and Employee Engagement on Employee Satisfaction, as well as to examine the moderating role of employee engagement in the relationships between organizational justice and WLB with employee satisfaction. Using a quantitative approach, data was collected from respondents who are employees in an organization and analyzed using Structural Equation Modeling (SEM). The results show that organizational justice, WLB, and employee engagement positively and significantly impact employee satisfaction, indicating that perceptions of fairness, balance between work and personal life, and emotional attachment to the job directly enhance employee satisfaction. However, employee engagement did not prove to be a significant moderating variable in the relationships between organizational justice and WLB with employee satisfaction. This finding suggests that organizational justice and WLB alone are strong enough to influence employee satisfaction without the need for employee engagement as a moderating factor. This study provides important implications for organizations to improve employee satisfaction through the implementation of fair policies, support for work-life balance, and fostering employee engagement.